Efficacy of four different left atrial appendage closure techniques during cardiac surgery—A transesophageal echocardiography follow-up studyCentral MessagePerspective - Johannes Petersen, MD; Henrike Böning, MD; Sevenai Yildirim, MD; Yousuf Alassar, MD; Yalin Yildirim, MD; Ilia Bazhanov, MD; Christoph Sinning, MD; Hermann Reichenspurner, MD, PhD; Simon Pecha, MD (JTCVS Techniques)
Objective: Closure of the left atrial appendage (LAA) is a routine part of atrial fibrillation ablation surgery and significantly reduces stroke rates. Different LAA-closure techniques are used in cardiac surgery with variable results reported. We therefore evaluated the efficacy of 4 different LAA-closure techniques in patients undergoing cardiac surgery. Methods: In total, 149 patients who underwent concomitant LAA closure during cardiac surgery between 2015 and 2019 were included in this retrospective transesophageal echocardiography study. Four different LAA-closure techniques were evaluated: LAA clipping (n = 62), suture ligation (n = 28), stapler resection (n = 30), and surgical LAA excision (n = 29). Successful LAA closure was defined as absence of LAA perfusion and absence of a stump greater than 10 mm. Results: The mean patients age was 68.7 ± 9.4 years; 61.7% were male. No complications related to LAA closure were observed. Mean follow-up was 36.5 ± 8 months. Transesophageal echocardiography follow-up showed the following LAA closure success rates: LAA clip 98.4%, surgical excision 93.1%, stapler resection 76.6%, and suture ligation 39.2%. Suture ligation resulted in a high rate of recanalization (50%) and residual stumps (10.8%), whereas stapler resection resulted in a high rate of residual stumps (23.4%). Overall, 4 patients (2.7%) had a stroke during follow-up. In detail, 2 of 27 (7.4%) patients with unsuccessful LAA closure had a stroke, whereas 2 of the 122 (1.6%) patients with successful LAA closure had a stroke. Conclusions: In our study, LAA clipping and surgical LAA excision proved to be both successful LAA-closure methods. External LAA ligation and stapler resection resulted in low rates of successful LAA closure and should be avoided.